SINKRONISASI PENGATURAN KEWENANGAN CABANG RUTAN BNN TERHADAP PP NOMOR 58 TAHUN 1999 DALAM KERANGKA SISTEM PEMASYARAKATAN - Markus Marselinus Soge (Legacy: Jurnal Hukum dan Perundang-Undangan, 2021)
The responsibility of organizing the correctional system includes the construction of inmates and the treatment of prisoners at the Directorate General of Corrections, but in practice, prisoners are not always in Rutan or Rutan Branch owned by Kemenkumham. BNN also manages Rutan Branch which is regulated in BNN Head Regulation No. 6 of 2016 concerning Prisoner Supervision. The problem here is how the synchronization level of the regulation of the authority of Rutan Branch of BNN against PP No.58 of 1999 within the framework of the correctional system. Normative legal research methods with legal approaches are used in this paper, and also used secondary data, namely primary and secondary legal materials. The data is collected by library study techniques, then qualitatively analyzed with legal interpretation. The results of the study are using guidelines for evaluation of legislation, especially table 3 assessment with variable 'authority' then the BNN Head Regulation No. 6 of 2016 is unsynchronized with PP No.58 of 1999 in the indicator 'there are arrangements about the same authority on 2 (two) or more regulations whose hierarchy is different, but the implementing agencies are different'. It is recommended that the Directorate General of Corrections of Kemenkumham can coordinate with BNN to discuss the unsynchronized of the authority arrangements of the Rutan Branch of BNN related to the supervision of prisoners to strengthen the implementation of the correctional system.